Perception of Physicians Working in Chile Toward Assisted Suicide and Euthanasia: A Nationwide Cross-Sectional Study - Yelson Alejandro Picón-Jaimes; Javier Esteban Orozco-Chinome; Iván David Lozada-Martínez; Sandra Mass-Ramirez; Carlos Iván Higuera-Cetina; Lina María Montaña-Gómez; Luis Rafael Moscote-Salazar; Alexis Rafael Narvaez-Rojas (SAGE Publishing, 2022)
Introduction: Assisted suicide and euthanasia are controversial issues today and have been throughout the history of humanity, mainly because there are individuals for and against them. Currently, the legalization of these practices is being discussed in Chile, and the perception of physicians regarding this issue is unknown. Therefore, this study aimed to assess physicians' perception of Chile's euthanasia and assisted suicide. Methods: A nationwide cross-sectional study was carried out in Chile. A questionnaire of physicians' attitudes and opinions on assisted suicide and euthanasia was used. The population was the doctors who work in Chile, and the sample was convenient with a sample calculation of 384 physicians. About 20 variables were considered and included in a form created through the Google forms option, which was distributed through social networks: LinkedIn, Facebook, Twitter, and WhatsApp. To guarantee the anonymity of the participants, the option to request and remember the participant's email was deactivated. A generated database allowed the quantitative analysis of the variables and their expression through frequencies, percentages, and graphs. The European University of the Atlantic's research ethics committee approved this study as stated in the document CE-55 of March 2021. Results: A total of 410 physicians were surveyed. 50.7% (n = 208) of the participants identified themselves as men, and 69.8% (n = 286) were Chilean. The city of Santiago was the area of residence of 72.9% (n = 299) of the participants. About 34.6% (n = 142) of participants were general practitioners, and 39.3% (n = 161) of the physicians had more than 20 years of experience. About 68.7% had favorable attitudes toward euthanasia and 54.4% toward assisted suicide; However, although the majority favored legalizing euthanasia and assisted suicide, approximately 48.8% stated that they would not participate in an assisted suicide procedure. Conclusions: There was evidence of support for the implementation and legalization of euthanasia and assisted suicide by physicians in Chile. However, there are still professionals who have not yet decided on a definitive position on these practices.